Effects of Early Childhood Education on Children with Hearing Impairments in Special Schools in Kiambu, Murang’A and Nyeri Counties, Kenya - Loise W., Chege; Wamocho, Franciscah I.; Orodho, John Aluko (Journal of the American Academy of Special Education Professionals, 2014)
This study sought to find out the effects of Early Childhood Education on children with hearing impairment (HI). Vigotsky’s theory of cognitive development guided the study. Descriptive survey method was used. Target population included children with HI between ages 3-6 years and their parents, teachers, head teachers all from special schools in selected districts. Purposive sampling was used to select schools, classes, children, teachers and head teachers while convenience sampling was used to select parents. Interview schedules were used for head teachers, pre-primary teachers and for parents. The instruments were pre-tested for validity and reliability. Split-half technique was used to assess the instruments’ reliability while validity was determined after it was read through with the representative respondents. Findings revealed that teachers played their role effectively but delays by parents in enrolling their children for ECDE [early childhood development and education] during the required early child years curtailed adequate effect of ECDE on children with HI.